2011
DOI: 10.1117/1.3560513
|View full text |Cite
|
Sign up to set email alerts
|

Increase of reduced nicotinamide adenine dinucleotide fluorescence lifetime precedes mitochondrial dysfunction in staurosporine-induced apoptosis of HeLa cells

Abstract: Abstract.In vivo noninvasive detection of apoptosis represents a new tool that may yield a more definite diagnosis, a more accurate prognosis, and help improve therapies for human diseases. The intrinsic fluorescence of reduced nicotinamide adenine dinucleotide (NADH) may be a potential optical biomarker for the apoptosis detection because NADH is involved in the respiration for the mitochondrial membrane potential ( ) formation and adenosine-5'-triphosphate (ATP) synthesis, and the depletion of and ATP level … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
31
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(45 citation statements)
references
References 33 publications
(47 reference statements)
14
31
0
Order By: Relevance
“…These results are consistent with earlier work from Ghukasyan et al that showed a significant increase of protein-bound NADH occurred only in apoptosis that caused an increase fluorescence lifetime to 3.6 ns [105]. Wang et al further used 5-ALA-mediated PDT to induce cell apoptosis and have a consistent finding as STS-induced apoptosis (increased NADH lifetime) [108]. With the alteration of fluorescence properties of endogenous fluorophores during apoptosis, it is feasible to perform noninvasive treatment monitoring and detection of cell death by considering both the changes of fluorescence lifetimes from photosensitizer (the drug-molecular interactions), and the endogenous fluorophores (the treatment effect).…”
Section: Endogenous Fluorophoressupporting
confidence: 91%
“…These results are consistent with earlier work from Ghukasyan et al that showed a significant increase of protein-bound NADH occurred only in apoptosis that caused an increase fluorescence lifetime to 3.6 ns [105]. Wang et al further used 5-ALA-mediated PDT to induce cell apoptosis and have a consistent finding as STS-induced apoptosis (increased NADH lifetime) [108]. With the alteration of fluorescence properties of endogenous fluorophores during apoptosis, it is feasible to perform noninvasive treatment monitoring and detection of cell death by considering both the changes of fluorescence lifetimes from photosensitizer (the drug-molecular interactions), and the endogenous fluorophores (the treatment effect).…”
Section: Endogenous Fluorophoressupporting
confidence: 91%
“…Between the early demonstrations in the 1990's and the present day, more than 1500 NAD(P)H fluorescence lifetime imaging studies have been published (Google Scholar), describing changes in the lifetime characteristics of live-cell NAD(P)H fluorescence in situations ranging from the onset of apoptosis [166], [170], [171], necrotic deterioration of skin [172] and wound healing [173] to stem cell differentiation [174], blood-glucose sensing [175] and aggregation of α- syn uclein in Parkinson’s disease [176]. However, until recently, the mechanisms linking the known metabolic shifts in these biological models to the changes in NAD(P)H lifetime were largely unknown, limiting their value as a biomedical assay.…”
Section: Practical Application Of Live-cell Nad(p)h Fluorescencementioning
confidence: 99%
“…32 The free/bound NADH ratio was suggested to dominate the change of NADH fluorescence lifetime. 31,33 Therefore, our observed increase in fluorescence NADH lifetime during osteogenic differentiation of hMSCs was possibly attributed to NADH interacting with respiration enzymes complex proteins, particularly Complex I. We analyzed the expression levels of protein subunits of respiratory enzyme Complex I-V by Western blot analysis as shown in Fig.…”
Section: Expression Of Respiratory Enzyme Complex Proteins Increased mentioning
confidence: 99%
“…29,31 An aliquot of 4 × 10 5 cells was re-suspended in 330 μl of assay buffer (125 mM sucrose, 65 mM KCl, 2 mM MgCl 2 , 20 mM phosphate buffer, pH 7.2), and the cell suspension was transferred into the respiration chamber at 37°C with a water circulation system. An aliquot of 0.0004% digitonin was added to permeablilize the outer membrane of mitochondria.…”
Section: Measurement Of Oxygen Consumption Ratementioning
confidence: 99%